Hubungan Antara Kontrol Diri Dan Konformitas Dengan Prokrastinasi Akademik - Novita Alya Ananti; Siti Aulia Rahmah; Vazha Dwi Putri; Lucky Purwantini (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Academic procrastination, the act of delaying academic tasks, is prevalent among students, as evidenced by the research of Solomon and Rothblum (1984) and Knaus (2002). Factors such as self-control and conformity influence this procrastination. This study, involving 143 psychology students from semesters 1, 3, & 5 at Universitas Islam 45 Bekasi, employs a quantitative correlational method. The results of the linearity test indicate a significant relationship between self-control and academic procrastination (p < 0.05), but no significant linear relationship between conformity and academic procrastination. Consequently, it is concluded that there is a correlation between self-control and academic procrastination in these students.